2022 IEEE 28th International Conference on Engineering, Technology and Innovation (ICE/ITMC) &Amp; 31st International Associati 2022
DOI: 10.1109/ice/itmc-iamot55089.2022.10033258
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of design in virtual reality across the variation of training degree and visual realism

Abstract: Research showed that immersive technologies can significantly improve the design process. However, it is important to consider the ease of implementation of solutions (e.g. price, simplicity). Therefore, the objective of this study was to analyze the uses of two types of virtual environments that are relatively simple to implement: a basic model of a room and its 3D scan. Participants made sketches using a virtual reality application, provided by the instructors, in each of the two different VR environments. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Figure 3 shows a summary of the results. These data are related to a study done on the same software (Fleury et al 2022).
Figure 3. Schematic representation summary of the results (task 3) * p ≤ .05; ** p ≤ 0.01.
…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 3 shows a summary of the results. These data are related to a study done on the same software (Fleury et al 2022).
Figure 3. Schematic representation summary of the results (task 3) * p ≤ .05; ** p ≤ 0.01.
…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have already highlighted collaborative case studies (e.g., de Klerk et al 2019; Safin 2020; Fleury et al 2022) involving lay people in a design process via a VR sketching tool. However, to our knowledge, few studies seem to have focused on the skills needed to use VR sketching compared to traditional sketching, especially with non-designers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the continuity of these first works, the research team explored the potential of virtual reality, on the same buildings in renovation. Thus, [10] explore the potential contribution of VR immersion in a 3D scan of a room to imagine and sketch in 3D ideas for layouts. During this research, the authors identified the importance of training participants to be comfortable using the tool.…”
Section: B Co-create / Co-design With Immersive Technologies and How ...mentioning
confidence: 99%
“…Within the framework of the EU project, six members of the consortium (two SMEs, one large company, three universities) are developing as a "multi-sided" platform [8], for creativity and customization of furniture or room layouts by integrating Augmented Reality (AR) and Virtual Reality (VR) into the co-design process (Fig. 1, a) and a priori facilitating the involvement of users in creating their own product, working with designers and / or manufacturers [9,10].…”
Section: Introductionmentioning
confidence: 99%